La noción de víctima a la luz de la jurisprudencia de la corte interamericana de derechos humanos (2018)
The victims throughout history have been at the center of the world debate, in which the defense of them has been promoted through the promulgation of normative instruments and the strengthening of judicial institutions for the sanction of the States. Thus, in the resolution of legal problems, the Inter-American Court of Human Rights (hereinafter IACHR), as an international judicial tribunal legitimized to apply and interpret the American Convention on Human Rights, has conceived that the concept of victim implies an injury of human rights by the States Parties, recognized in a judicial decision; conception that has transcended the recognition of relatives as indirect victims, under the assumption of the functional balance between the exercise of power and the guarantees of obligations, both negative and positive of the States, for individuals and for entire populations. From this perspective, in the present work the conception of collective victims will be addressed from the jurisprudence of the IACHR, and for that purpose an analysis of the judgments that this Court has issued on the subject will be made, reviewing what has been said about it and the evolution in its conception.